Origem, consolidação e internacionalização dos grupos Mexichem e Tigre - Leandro Bruno Santos (Universidad Nacional Autónoma de México, 2016)
In the last three decades, the peripheral countries have played an increasing role on the international scene, mainly with regard to Foreign Direct Investment Flows ( FDI ). This increase is due not only to the economic crisis in developed economies, but also to the rapid economic expansion of countries like Brazil, China and India, which constituted a solid basis for that their companies continued to expand abroad. From the 1990s, PVC pipes and fittings industry in Latin America witnessed an intense process of concentration and centralization of capital, which led to the internationalization of the Tigre, Mexichem e Alexis Latinoamerica business groups, respectively. The productive internationalization was a response to three factors, inclu- ding high concentration of the internal market, stagnation of the construction industry and unrestrained economic libe- ralization, culminating in the deepening of the oligopolistic competition in the various spatial scales. This article aims to analyze the productive internationalization strategies adop- ted by Mexichem and Tigre business groups, respectively, largest manufacturers of PVC pipes and fittings in Mexico and Brazil. In order to achieve this purpose, we adopted as methodological procedures the bibliographic selection and reading, data collection and compiling provided by the groups in their annual reports and information disclosed by the online news portal targeted to the business markets (Exame and CNN Expansión), systematization of data and information in the light of theoretical reflections relating to internationalization and market structures of the pipes and fittings industry. Throughout the text are highlighted different trajectories, main branches, overseas operations and international integration forms of the business groups. Two important conclusions are indicated. First, the main factors that led to the productive internationalization of both groups were the growing need for new dynamic spaces of capital accumulation, due to the economic slowdown and the market concentration, and participation in the struggle for oligopolistic concentration of the PVC pipes and fittings industry on a global scale. Second, multi-territorial strategies of productive internationalization (sectoral and market entry) reflect the consolidation trajectories of these business groups in their respective markets. Our original idea is that the distinctive capabilities built by the groups during the consolidation process in the domestic market have been used to change the patterns of international competition in the PVC pipes and fittings industry at various scales. Therefore, our thesis is that the process of internationalization of the two groups is related to the construction of specific skills that must be understood in the light of factors such as consolidation in the domestic market, industry structure in which they operate and inter-capitalist competition (creative destruction, concentration and centralization of capital) on a global scale.